Penerapan Model Pembelajaran Konstruktivisme Melalui Metode Eksperimen dan Demonstrasi Terhadap Hasil Belajar Siswa pada Materi Fluida - Fartina, Fartina; Hizbi, Tsamarul; Zahara, Laxmi; Sapiruddin, Sapiruddin; Yunus, Muhammad (Kappa Journal, 2023)
This study aims to determine whether there is an influence of the constructivism model through experimental and demonstration methods on student learning outcomes on fluid material at SMA Negeri 1 Suralaga in the 2022/2023 academic year". This study uses an experimental method with a posttest-only control design, which only provides a post-test at the end of the treatment. The population in this study were all students of class XI IPA SMA Negeri 1 Suralaga. Meanwhile, the sample in this study was class IPA 1 as the experimental group and class XI IPA 2 as the control group. The two samples were randomly selected with either Cluster Random Sampling (Area Sampling). The experimental group was taught physics using the constructivism model through experimental and demonstration methods and the control group was taught physics using the conventional model. The research data were analyzed using a one-sided t-test. Based on the results of the study obtained tcount (2,73 ) > ttable (1,68 )   at a significant level  is received. So, it can be concluded that there is an influence of the constructivism model through experimental and demonstration methods on student learning outcomes on fluid material.